TEACHING PUPILS WHO HAVE BEHAVIOUR DISORDERS IN A NORMAL CLASSROOM SETTING - Okubanjo, Olusola O. (Sokoto Educational Review, 2020)
Children behaviour problems have become a crucial issue of discussion for some time now. This is because children pose series of problems to their parents, teachers and the society. Within the school system, teachers are confronted with the tasks of how to discipline, as well as, present instructions to these children along with the normal pupils in the class, for better learning outcomes. Considering the fa c t that the introduction of the Universal Basic Education (UBE) Scheme now gives educational access to several children of school going age, it follows therefore, that there will be an increase in the manifestation of multifarious behaviour problems of pupils. This paper highlights the strategies that could be adopted by primary school teachers in the teaching-learning process towards ensuring better classroom adjustment and academic achievement of pupils with behaviour disorder within the group of normal children.